Crimequest, A CLIL Approach of ”Learning on Gaming” to Improve Science Education and Language Learning - Ercolino, Immacolata; Maraffi, Sabina; Sacerdoti, Francesco Maria (European Scientific Journal, ESJ, 2018)
This work focuses on Science teachinginhigh school using the Content and Language Integrated Learning (CLIL) approach. Students need to be educated as science active citizensso that to be able to close the skills gap between science literacy and societal requirements . In fact it is important to combat misconceptions in order to face challenges that daily involve society and request skills and knowledge in science. Teachers need new insights to foster youngsters learning and to enhance digital literacy and competences and need to update them continuously. The authors have realized a role playing computer game called CrimeQuest with a specific Role Playing Engine, which involves all students into the adventure through their personal mobiles or tablets, with a complete interaction of the whole class with the game. The students interact with the system using their own smartphones and tablets with a new technology, which collects the individual answers. At the same time the system calculates the overall response according to the criterion of majority voting. The game works without Internet and is realized with a specific software engine that interprets a text file as the adventure plot, with text-to speech multi-language voices. Learning on gaming through our Computer Class Role Playing Game is a way to realize “authentic learning”: it lets students feel themselves on a Crime Scene, involving them in their own learning. In this way foreign language becomes a vehicular tool to discover new topics and their specific glossary: it is a CLIL approach, in which the not language subject is taught through a foreign language.